Multi-Frequency Databases for AGN Investigation—Results and Perspectives - La Mura, Giovanni; Berton, Marco; Chen, Sina; Ciroi, Stefano; Congiu, Enrico; Cracco, Valentina; Frezzato, Michele; Rafanelli, Piero (Frontiers in Astronomy and Space Sciences, 2017)
Active Galactic Nuclei (AGNs) are characterized by emission of radiation over more than 10 orders of magnitude in frequency. Therefore, the execution of extensive surveys of the sky, with different types of detectors, is providing the attractive possibility to identify and to investigate the properties of AGNs on very large statistical samples. Thanks to the large spectroscopic surveys that allow detailed investigation of many of these sources, we have the opportunity to place new constraints on the nature and evolution of AGNs and to investigate their relations with the host systems. In this contribution we present the results that can be obtained by using a new interactive catalogue that we developed to investigate the range of AGN spectral energy distributions (SEDs). We present simple SED models based on data collected in the catalogue and discuss their relations with optical spectra obtained by follow up observations. We compare our findings with the expectations based on the AGN Unification Model, and we discuss the perspectives of multi-wavelength approaches to address AGN related processes such as black hole accretion and acceleration of relativistic jets.